Correlation analysis between physical activity and depressive tendencies among occupational groups: an isotemporal substitution approach - Yihua Liu; Haoxiang Lin; Hao Zhang; Xiaoyue Zhang; Shengli Yin (BMC, 2023)
Abstract Objectives Sedentary behaviour (SB) and physical activity (PA) have been shown to be associated with depression. However, behaviours, such as PA, occupy a portion of an individual's 24-h day. Thus, an increase in time for one behaviour takes away time from another. Previous evidence suggests that it would be more appropriate to shift the focus to the importance of reallocating time spent in sedentary behaviour to time spent in physical activity. The aim of this study was to analyse the mutual replacement effect of different health behaviours on depressive tendencies by isotemporal substitution modelling (ISM) under the objective condition of considering a limited 24-h day. Second, we aimed to further explore the potential association between excessive or insufficient sleep duration and depressive symptoms. Methods A total of 10656 employees from 79 companies in four provinces of China participated in this survey. The Center for Epidemiological Studies Depression Scale (CES-D) was used to measure workers' depressive tendencies. The duration of various types of physical activity was self-reported by workers based on the International Physical Activity Questionnaire (IPAQ). ISM was used to assess the associations of time spent in different activities on displacement of equivalent time spent on other activities with depression risk. Results A total of 10656 participants (89.5% of the sample) were included in the analysis. The ISM found that a 30-min unit of SB replaced with walking (OR, 95% CI: 0.83, 0.77-0.88), sleep (≤ 8 h) (OR, 95% CI: 0.77, 0.74-0.79), moderate physical activity (MPA) (OR, 95% CI: 0.87, 0.81-0.93) and vigorous physical activity (VPA) (OR, 95% CI: 0.91, 0.84-0.99) was significantly and negatively associated with the risk of depressive tendencies. When sleep duration was less than 8 h, each additional half hour of sleep time was significantly associated with a lower risk of depressive tendencies, and this association was no longer significant after 8 h. Conclusion Prolonged SB is common in the current workplace in China. Replacing an average of 30 min per day of SB with VPA and MPA, even walking is associated with less depression among workers. In addition, insufficient daily sleep is also an important risk factor for workers' depressive tendencies. These findings provide valuable evidence to promote mental health among occupational groups and support the development of healthy workplaces.